1998
DOI: 10.1016/s0736-5748(98)00049-5
|View full text |Cite
|
Sign up to set email alerts
|

Emigration of neuroepithelial cells from the hindbrain neural tube in the chick embryo

Abstract: It is generally believed that after the emigration of neural crest, the neuroepithelial cells of the neural tube are committed to differentiate only as neurons and supporting cells of the central nervous system. Neural crest cells arise from the dorsal portion of the developing neural tube and contribute to the formation of the peripheral nervous system and a variety of non-neural structures. In contrast to this view we have recently shown, by focal application of the vital dye Dil in duck embryos, that an add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 19 publications
3
27
0
Order By: Relevance
“…However, these embryos showed no labeling of cardiomyocytes, striated muscle, or endothelial cells. This finding confirms the results of Yaneza et al (2002) and Boot et al (2003), who were unable to confirm the presence of a late-emerging population of multipotential ventral hindbrain (VENT) cells (Sohal et al, 1998).…”
Section: Critique Of Methodssupporting
confidence: 89%
“…However, these embryos showed no labeling of cardiomyocytes, striated muscle, or endothelial cells. This finding confirms the results of Yaneza et al (2002) and Boot et al (2003), who were unable to confirm the presence of a late-emerging population of multipotential ventral hindbrain (VENT) cells (Sohal et al, 1998).…”
Section: Critique Of Methodssupporting
confidence: 89%
“…By using three different labeling techniques, i.e., focal application of the vital dye DiI, homeobox gene Islet-1 expression pattern, and recombinant retroviral labeling, it was found that some neural tube cells also emigrate from the cranial neural tube in the chick and duck embryos (Sohal et al, 1996(Sohal et al, , 1998a. They originate in the ventral portion of the hindbrain and emigrate at the site of attachment of the cranial nerves, considerably after the emigration of neural crest is finished.…”
Section: Introductionmentioning
confidence: 99%
“…Third, they do not express the neural crest antigen HNK-1. Fourth, they differentiate into all four basic tissues: the nerve, muscle, connective, and epithelium (Bockman and Sohal, 1998;Sohal, 1998;Sohal et al, 1996Sohal et al, , 1998aSohal et al, ,b, 1999a. This cell population has been named as the Ventrally Emigrating Neural Tube cells, or VENT cells, on the basis of its origin and emigration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations